If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 5 = 32 Reorder the terms: 5 + x = 32 Solving 5 + x = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 32 + -5 Combine like terms: 5 + -5 = 0 0 + x = 32 + -5 x = 32 + -5 Combine like terms: 32 + -5 = 27 x = 27 Simplifying x = 27
| -11x-x^2=0 | | 4x+1-6x=2(x+3)-4x | | (2x+4)3=x+4 | | 9m-m^2=0 | | 2b(3b+4)+6b(2b+1)= | | 9(c+5)=8(c+4) | | 3(5+c)=2(c-6) | | 7w-w^2=0 | | -6x+2+2x+9+x=5x+10-6x+11 | | 6x^3+9x^2-27x= | | 2(4x+3)3=0 | | x(-11-x)=0 | | w(-13+w)=0 | | 3x/2+x/6=-5/3 | | x-(-21)=23 | | -8b+b^2=0 | | -4+r=3r | | 8x^3+20x^2-48x= | | 8b+b^2=0 | | x-3000-(3000-3/5)=1500 | | r+2r=4r(2) | | 4(x+3)=3(x-2)+x+18 | | 2x+4x+3x-6x=0 | | -5x+3y+2-8+3x-5y= | | 2a(3a+4)+6a(2A+1)= | | -13w+w^2=0 | | 8x-17=23 | | -x(6+3-2)=x(2+4)+8 | | -14+x=33 | | 9(x-2)+6(x-3)=0 | | 5x+10y=5750 | | 5x(3x+2y)= |